2018
DOI: 10.1161/circresaha.118.313089
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast-Specific TGFβ Receptor II Signaling in the Fibrotic Response to Cardiac Myosin Binding Protein C-Induced Cardiomyopathy

Abstract: Rationale: Hypertrophic cardiomyopathy occurs with a frequency of about 1 in 500 people. Approximately 30% of those affected carry mutations within the gene encoding cardiac myosin-binding protein C (cMyBP-C). Cardiac stress, as well as cMyBP-C mutations, can trigger production of a 40kDa truncated fragment derived from the amino terminus of cMyBP-C (Mybpc340kDa). Expression of the 40kDa fragment in mouse cardiomyocytes leads to hypertrophy, fibrosis and heart failure. Here we use genetic approaches to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 48 publications
(87 reference statements)
3
40
0
Order By: Relevance
“…However, recent evidence from mouse models of genetic cardiomyopathies has challenged the notion that ECM remodeling is an innocent companion. In transgenic mouse models of HCM, myofibroblast-specific disruption or pharmacologic inhibition of TGF-β signaling reduced myocardial fibrosis, prolonged survival, and preserved cardiac function 246 , 247 . These observations may suggest that activation of a fibrogenic program may exacerbate dysfunction and worsen outcome in subjects with sarcomeric mutations.…”
Section: The Ecm In Genetic Cardiomyopathiesmentioning
confidence: 99%
“…However, recent evidence from mouse models of genetic cardiomyopathies has challenged the notion that ECM remodeling is an innocent companion. In transgenic mouse models of HCM, myofibroblast-specific disruption or pharmacologic inhibition of TGF-β signaling reduced myocardial fibrosis, prolonged survival, and preserved cardiac function 246 , 247 . These observations may suggest that activation of a fibrogenic program may exacerbate dysfunction and worsen outcome in subjects with sarcomeric mutations.…”
Section: The Ecm In Genetic Cardiomyopathiesmentioning
confidence: 99%
“…Interestingly, even though both cardiac fibroblast-specific deletion of Tgfbr1/2 and Smad2/3 significantly reduced cardiac fibrosis induced by transverse aortic constriction (TAC), only the deletion of Tgfbr1/2 in cardiac fibroblasts ameliorated cardiac hypertrophy and resulted in a functional improvement at 4 and 12 weeks after TAC (Khalil et al, 2017). Similarly, myofibroblast-specific Tgfbr2 deletion led to improved cardiac function in mouse models of proteotoxic cardiac disease and cardiac myosin binding protein C-induced cardiomyopathy (Bhandary et al, 2018;Meng et al, 2018). Studies conducted by another group using Postn-Cre-mediated myofibroblast-specific deletion of Smad3 and Smad2 found that while deletion of Smad2 temporarily improved cardiac function around 7 days after myocardial infarct (MI) in mice, deletion of Smad3 caused a reduction in cardiac function 28 days after MI (Kong et al, 2018;Huang et al, 2019).…”
Section: Targeting Tgfβ and Related Signalingmentioning
confidence: 99%
“…This complex stimulates ubiquitination and degradation of P53, thereby promoting cell cycle progression and proliferation of CFs [140]. While TGFβ signaling is essential to initiate CF activation, a recent study demonstrated that ablation of TGFβR2 in activated Postn+ CFs reduced fibrosis, indicating that sustained TGFβ signaling is required to maintain CF activation [154].…”
Section: Tgfβ Regulation Of Fibroblast Plasticity and Proliferationmentioning
confidence: 99%